2019
DOI: 10.1021/acsbiomaterials.9b00414
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Fabrication, Microstructure, and in Vitro and in Vivo Investigations of a High-Performance Multilayer Coating with External, Flexible, and Silicon-Doped Hydroxyapatite Nanorods on Titanium

Abstract: A high-performance multilayer coating with external, flexible, and silicon-doped hydroxyapatite (Si-HA) nanorods was designed using bionics. Plasma electrolytic oxidation (PEO) and the microwave hydrothermal (MH) method were used to rapidly deposit this multilayer coating on a titanium (Ti) substrate, applied for 5 and 10 min, respectively. The bioactive multilayer coating was composed of four layers, and the outermost layer was an external growth layer that consisted of many Si-HA nanorods with a singlecrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…We can observe that there is no fracture of the peri -implant bone 2 weeks after the operation, indicating that the implant can be used for replacement and load-bearing situations, such as dentistry and orthopedics. 53 The regenerated bone structure around the implant was reconstructed and analyzed by μ-CT 4 weeks after implantation. Assessing changes in complex bone formation around implants is more intuitive due to the natural radiopacity of Ti materials.…”
Section: Resultsmentioning
confidence: 99%
“…We can observe that there is no fracture of the peri -implant bone 2 weeks after the operation, indicating that the implant can be used for replacement and load-bearing situations, such as dentistry and orthopedics. 53 The regenerated bone structure around the implant was reconstructed and analyzed by μ-CT 4 weeks after implantation. Assessing changes in complex bone formation around implants is more intuitive due to the natural radiopacity of Ti materials.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the MAO treatment process have been reported in our previous studies. [40][41][42] For the MH treatment, the MAO specimens were treated in a reaction kettle containing 40 mL of different concentrations of NaOH solution, followed by microwave hydrothermal treatment at 200 C for 10 min (XH-800S, Beijing Xianghu Science and Technology Development Co., China). During the MH treatment process, the microwave frequency and power were set to 2450 MHz and 800 W, respectively.…”
Section: Specimen Fabricationmentioning
confidence: 99%
“…The previous literature study reported that the ionic substituted HA nanorods such as Sr, Si and F ions had higher solubility. 42,43 In addition, the Sidoped HA crystals had higher solubility than the pure HA crystals because the substitution of PO 4 3À by SiO 4 3À ions could change the crystal structure of the HA phase. Therefore, the Si-HA crystals were easily degraded owing to the formation of the crystal defects aer the substitution.…”
Section: Microstructure Of Mh-treated Mao Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed that microwave heating could achieve better performance than conventional heating in materials synthesis and processing. [12][13][14][15] Microwave energy is characterized by the volumetric thermal effect due to its large wavelength, which allows the energy to be absorbed in a large material volume (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%